Asiatic Mode of Production : Considerations on Ancient Egypt - Zingarelli, Andrea Paula (2015)
This chapter will inquire into the validity of Marx and Engels’s elaborations on the Asiatic mode of production – with their contradictions and the modifications they went through over time – in connection with the historical process of an ancient state. It will also analyse in part how these elaborations were later received and transformed by the more relevant Marxist historiography. More precisely, our aim is to analyse the Asiatic mode of production from the particular perspective of the dominant relations of production in pharaonic Egypt. The goal of our inquiry does not merely imply a recourse to the ‘facts’ of Egyptian history in the empirical sense so strongly criticised by Hindess and Hirst, but a recourse to an abstraction of the historical process, which is not the same as the abstraction of an ideal elaboration devoid of historical meaning. We will thus focus on a certain social formation and on the economic, social, political and ideological relations that appear historically in consonance with the dominant Asiatic mode of production, and with other relations typical of other modes of production.